Bibliometric Analysis of the Literature on the Development and Contribution of SMEs In the Development of the National Economy - Mihaela TULVINSCHI; Adriana STRATU; Cristina Gabriela COSMULESE; Monica Laura ZLATI (Communications of International Proceedings, 2021)
The aim of this paper is to carry out a bibliometric analysis to study the evolution and contribution of SMEs in the economic development of Romania after the economic and financial crisis of 2007. To this end, we have analyzed the effects of the pandemic by field of activity, the risks of the pandemic on activity and its impact on the labour market. The research methodology consisted in using a database created with the Web of Science platform between 2019-2020, through which 236 scientific papers on the role and contribution of SMEs in the economy and the crises that have had long-lasting effects both at macroeconomic and microeconomic level emerged, which were analyzed and centralized in the VOSviewer program.
Keywords: SME; Economic Crisis; Employment; GDP; Economic Risks.